The Steam Bending Properties of Indian Timbers - Rehman, M. A.; Kishen, Jar; Kukreti, D. P. (Indian Forester, 1956)
The results of the first series of tests carried out on the steam bending properties of 19 Indian timber species are described. Out of these, benteak (Lagerstroemia lanceolata) has been found to be the best, followed by rosewood (Dalbergia latifolia). Elm (Ulmus spp.) and karshu (Quercus semecarpifolia) are also good benders, but they are available in small quantities in the Himalayas and their extraction is difficult. Likely uses of these timbers are also suggested on the basis of their bending qualities and other properties.